Structural characterization of the hydrophobin SC3, as a monomer and after self-assembly at hydrophobic/hydrophilic interfaces. - de Vocht, M L (1998)
Hydrophobins are small fungal proteins that self-assemble at hydrophilic/hydrophobic interfaces into amphipathic membranes that, in the case of Class I hydrophobins, can be disassembled only by treatment with agents like pure trifluoroacetic acid. Here we characterize, by spectroscopic techniques, the structural changes that occur upon assembly at an air/water interface and upon assembly on a hydrophobic solid surface, and the influence of deglycosylation on these events. We determined that the hydrophobin SC3 from Schizophyllum commune contains 16-22 O-linked mannose residues, probably attached to the N-terminal part of the peptide chain. Scanning force microscopy revealed that SC3 adsorbs specifically to a hydrophobic surface and cannot be removed by heating at 100 degrees C in 2% sodium dodecyl sulfate. Attenuated total reflection Fourier transform infrared spectroscopy and circular dichroism spectroscopy revealed that the monomeric, water-soluble form of the protein is rich in beta-sheet structure and that the amount of beta-sheet is increased after self-assembly on a water-air interface. Alpha-helix is induced specifically upon assembly of the protein on a hydrophobic solid. We propose a model for the formation of rodlets, which may be induced by dehydration and a conformational change of the glycosylated part of the protein, resulting in the formation of an amphipathic alpha-helix that forms an anchor for binding to a substrate. The assembly in the beta-sheet form seems to be involved in lowering of the surface tension, a potential function of hydrophobins.